French Renaissance printing types : a conspectus - Vervliet, Hendrik D. L. (The Bibliographical Society : The Printing Historical Society ; Oak Knoll Press, 2010)
"A survey of all Roman, Italic, Greek, Hebrew, and Arabic typefaces made in France during the sixteenth century, describing the evolution of type-casting and letter-engraving and the methodology used. Illustrated with facsimiles of 409 typefaces with detailed descriptions including their first appearance in books or type specimens"--Provided by publisher.